One-pot method of synthesis and supercritical carbon dioxide drying of PVdF-HFP composite membranes - Martyla, Agnieszka; Przekop, Robert; Osinska-Broniarz, Monika; Walkowiak, Mariusz; Kopczyk, Maciej (European Journal of Chemistry, 2016)
This paper describes one-pot method of the synthesis and properties of composite polymer gel electrolytes based on poly(vinylidenefluoride-co-hexafluoropropylene) (PVdF-HFP). As the precursor of the inorganic filler tetraethyl orthosilicate (TEOS) and titanium tetra-n-butoxide (Ti(OC4H9)4) were used. The drying of membranes with fillers was carried out with supercritical CO2. The membranes and gel electrolytes have been examined structurally and electrochemically, showing favorable properties in terms of electrolyte uptake and electrochemical characteristics in Li-ion cells.